To Use Face Masks or Not After COVID-19 Vaccination? An Impact Analysis Using Mathematical Modeling - Kinyili, Musyoka; Munyakazi, Justin B.; Mukhtar, Abdulaziz Y. A. (Frontiers in Applied Mathematics and Statistics, 2022)
The question of whether to drop or to continue wearing face masks especially after being vaccinated among the public is controversial. This is sourced from the efficacy levels of COVID-19 vaccines developed, approved, and in use. We develop a deterministic mathematical model that factors in a combination of the COVID-19 vaccination program and the wearing of face masks as intervention strategies to curb the spread of the COVID-19 epidemic. We use the model specifically to assess the potential impact of wearing face masks, especially by the vaccinated individuals in combating further contraction of COVID-19 infections. Validation of the model is achieved by performing its goodness of fit to the Republic of South Africa's reported COVID-19 positive cases data using the Maximum Likelihood Estimation algorithm implemented in the fitR package. We first consider a scenario where the uptake of the vaccines and wearing of the face masks, especially by the vaccinated individuals is extremely low. Second, we consider a scenario where the uptake of the vaccines and wearing of the face masks by people who are vaccinated is relatively high. Third, we consider a scenario where the uptake of the vaccines and wearing of the face masks by the vaccinated individuals is on an upward trajectory. Findings from scenario one and scenario two, respectively, indicate a highly surging number of infections and a low recorded number of infections. For scenario three, it shows that the increased extent of wearing of the face masks by the vaccinated individuals at increasing levels of vaccine and face mask average protection results in a highly accelerated decrease in COVID-19 infections. However, wearing face masks alone also results in the reduction of the peak number of infections at increasing levels of face mask efficacy though the infections delay clearing.